Efeitos do extrato etanólico e aquoso das folhas de garcinia gardneriana em modelos experimentais in vivo - Espírito Santo, Bruna Larissa Spontoni do (2022)
Obesity is a growing health issue in the world, and its prevalence is rapidly increasing in developed and developing countries. The chronic study of medicinal plants in the treatment of non-communicable diseases has aroused the interest of researchers. Medicinal plants and their constituents may hold promise for the treatment of obesity and comorbidities. Various medicinal plants and their active anti-obesity constituents beneficial plants in vivo. Garcinia gardneriana (Planchon & Triana) Zappi (Clusiaceae), popularly known as bacupari, has bioactive phytochemical compounds, such as phenolic compounds, mainly flavonoids, xanthones and benzophenones that are present in the species. In this, this proposal was made the leaf of Bac (Garcin gardneriana) through a profile of bioactive diet characteristics, as well as evaluated the effects of the administration of different experimental models with consumption of consumption context. For the experiment, 130 male mice were divided into 7, fed the following groups of diets: Normal diet based on the standard Nuvital® diet, Normal diet based on AIN-93M, High fat diet (4% soybean oil and 31% lard ), High fat diet (4% soy oil and 31% lard) + Aqueous extract (200mg/kg), High fat diet (4% soy oil and 31% lard) + Aqueous extract (400mg/kg), High-fat diet (4% soybean oil and 31% lard) + Ethanol Extract (200mg/kg), High-fat diet (4% soybean oil and 31% lard) + Ethanol Extract (400mg/kg), all weekly and monitored in terms of feed consumption. During 8 weeks of treatment, food consumption was monitored and at the end of this period the animals were anesthetized and euthanized by exsanguination. In the blood, lipid profiles, blood glucose and cytokines were recorded. In the analysis of biomarkers, the cytokine IL-10 showed a higher value for the HF group, when compared to the other groups (p<0.001). For the MCP-1 cytokine, the groups that received a high-fat diet had higher values. The results reveal that the groups showed no difference in the total calories performed. The use of aqueous stress at 40mg/Kgideo improved triglycemic values and profile, inferring its possible use in the treatment of moderate-to-moderate stress and chronic non-communicable diseases such as diabetes.